2014
DOI: 10.1111/1365-2656.12285
|View full text |Cite
|
Sign up to set email alerts
|

Changes in host–parasitoid food web structure with elevation

Abstract: Summary1. Gradients in elevation are increasingly used to investigate how species respond to changes in local climatic conditions. Whilst many studies have shown elevational patterns in species richness and turnover, little is known about how food web structure is affected by elevation. 2. Contrasting responses of predator and prey species to elevation may lead to changes in food web structure. We investigated how the quantitative structure of a herbivore-parasitoid food web changes with elevation in an Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 66 publications
6
65
7
1
Order By: Relevance
“…This contrasts with patterns found for seed dispersal and pollinator networks across latitudinal gradients, in which reduced partner availability results in greater specialization [6]. However, decreased specialization with elevation has been observed for leaf miner–parasitoid interaction networks [38]. In contrast with our results, these antagonistic networks showed no change in connectance.…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts with patterns found for seed dispersal and pollinator networks across latitudinal gradients, in which reduced partner availability results in greater specialization [6]. However, decreased specialization with elevation has been observed for leaf miner–parasitoid interaction networks [38]. In contrast with our results, these antagonistic networks showed no change in connectance.…”
Section: Discussioncontrasting
confidence: 99%
“…A decline of parasitism towards higher elevations is likely, as the frequency of trophic interactions decreases polewards [59] and local elevation gradients reflect large-scale climatic gradients. To our knowledge, only two recent studies from subtropical Australia have addressed this topic and found a decrease of parasitism with elevation [18,46], which we support. Higher parasitism at lower and warmer lower elevation might be caused by higher attack rates of parasitoids, as demonstrated in controlled warming experiments [60].…”
Section: (C) Influence Of Elevation On Host-parasitoid Interactionssupporting
confidence: 81%
“…For the system studied and for other host-parasitoid systems (e.g. leaf miner-parasitoid [8,46] or aphid-parasitoid [47]), the biologically most relevant niches are probably food (i.e. food for hosts, hosts of parasitoids; see below) and shelter [4].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental temperatures, hibernation length, feeding activity, and food abundance strongly influence lizard distributions (Guisan and Hofer 2003). In particular, food web structure or properties (Albouy et al 2014;Maunsell et al 2015) and the effects of climate warming on biotic interactions will indirectly influence species distributions (Jeffs and Lewis 2013). Most lizard species in our study mainly eat a variety of insects and other invertebrates or a few plant species.…”
Section: Discussionmentioning
confidence: 96%